"Ecological-oriented consumption": a pluriactoral approach. (1st January 2000) - Zaccai, Edwin
We propose a model grouping the main factors that allow the success or failure of actions in ecological-oriented consumption to be assessed. Illustrated by some case studies, this model is then situated within a broader pluriactoral analysis, bringing together consumers, industries, and public authorities. We show that the conditions needed for the success of ecological-oriented choices by consumers are multiple. Therefore, these types of action may not, by far, be the only tool in changing consumption patterns. We suggest some roles that each group of actors may play in this respect, and their limitations.